LAJU INFILTRASI PADA AREAL PERTANAMAN WORTEL DI WILAYAH RURUKAN KECAMATAN TOMOHON TIMUR KOTA TOMOHON - Derek, Jery D.; Husain, Jailani; Lengkong, Jeanne E.; Kamagi, Yani E.B. (Soil and Environment Journal, 2021)
INFILTRATION RATE IN SOIL OF CARROT FARMING AREA AT RURUKAN, TOMOHON TIMUR DISTRICT, TOMOHON This study aims to determine the rate of infiltration in the carrot plantation of Rurukan area of Tomohon City. Infiltration rate measurement was carried out in the field of carrot plantation areas, which were treated with mulch (with code: BM), without mulch (BT) and untreated soil (B0) using the Guelph permeameter. Observations were made twice, namely at the beginning period of planting (35 DAP), and the period of before harvest (103). Results showed that the highest infiltration rate occurred in the first observation (35 DAP) by the treatment of using mulch (BM) which was 301.2 cm/hour, and the lowest rate was at the treatment of without using mulch (BT) and the control, or without treatment (B0) which was 226.2 cm/hour. For the second observation (103 DAP), the highest infiltration rate occurred in the treatment of without using mulch (BT) which was 226.2 cm/hour and the lowest in the treatment of using mulch (BM) which was 180.6 cm/hour. More increase the period of time, more decrease the infiltration rate until it becomes constant.